1999
DOI: 10.1159/000014121
|View full text |Cite
|
Sign up to set email alerts
|

Intracytoplasmic Sperm Injection Pregnancy with Trisomy 20p and Monosomy 22q in a Newborn Resulting from a Balanced Paternal Translocation

Abstract: In infertile men who carry a balanced reciprocal translocation, intracytoplasmic sperm injection (ICSI) may induce a pregnancy with an abnormal karyotype. This report describes a previously unreported paternal reciprocal translocation leading to a chromosomally unbalanced ICSI pregnancy. The triplet pregnancy resulted in 1 normal girl, 1 physically normal boy with the same balanced paternal translocation, and a severely malformed boy with trisomy 20p and monosomy 22q who died in the neonatal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Thirty-nine cases have been reported, all but two cases [Zumel et al, 1989;Molina-Gomes et al, 2006] diagnosed postnatally. Most partial trisomies result from reciprocal translocation [Taylor et al, 1976;Marcus et al, 1979;Funderburk et al, 1983;Lurie et al, 1985;Vamos et al, 1985;Zumel et al, 1989;Grammatico et al, 1992;LeChien et al, 1994;Belin et al, 1999;Oppenheimer et al, 2000;Wieczorek et al, 2003;Thomas et al, 2004;T€ umer et al, 2005;Brenk et al, 2007]. In a few cases, trisomy 20p results from parental inversion [Lucas et al, 1985;Bown et al, 1986;Molina-Gomes et al, 2006;Chaabouni et al, 2007] or the formation of isochromosomes [Sidwell et al, 2000].…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…Thirty-nine cases have been reported, all but two cases [Zumel et al, 1989;Molina-Gomes et al, 2006] diagnosed postnatally. Most partial trisomies result from reciprocal translocation [Taylor et al, 1976;Marcus et al, 1979;Funderburk et al, 1983;Lurie et al, 1985;Vamos et al, 1985;Zumel et al, 1989;Grammatico et al, 1992;LeChien et al, 1994;Belin et al, 1999;Oppenheimer et al, 2000;Wieczorek et al, 2003;Thomas et al, 2004;T€ umer et al, 2005;Brenk et al, 2007]. In a few cases, trisomy 20p results from parental inversion [Lucas et al, 1985;Bown et al, 1986;Molina-Gomes et al, 2006;Chaabouni et al, 2007] or the formation of isochromosomes [Sidwell et al, 2000].…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…The pregnancy of Meschede's case 9 (a female with t(10;14)) was reported to be uneventful. Belin et al (1999) reported a triplet pregnancy with a chromosomally normal girl, one physically normal boy with a balanced translocation and a severely malformed boy with partial trisomy 20p and monosomy 22q who died in the neonatal period. The father carried a previously unreported balanced translocation (20;22).…”
Section: Autosomal Reciprocal Translocationsmentioning
confidence: 99%
“…Translocations associated with infertility may involve virtually any chromosome, though the sex chromosomes are most frequently perturbed Meschede et al, 1998;Van der Ven et al, 1998;Causio et al, 1999;Belin et al, 1999;Giltay et al, 1999a, b;Peschka et al, 1999). Associated phenotypes range widely depending on the chromosomes involved.…”
Section: Structural Rearrangements (Translocations Deletions and Rings)mentioning
confidence: 99%
“…Translocations may be balanced with the genome remaining largely intact or unbalanced with chromosome loss. Because unbalanced translocations usually have a devastating effect on phenotype, patients carrying balanced rearrangements most commonly seek assisted reproduction (Mikkelsen, 1999;Belin et al, 1999;Giltay et al, 1999b). Some individuals may have compromised gonad function, but others may have normal fertility associated with a history of recurrent abortion or the birth of a child with an unbalanced chromosomal rearrangement.…”
Section: Structural Rearrangements (Translocations Deletions and Rings)mentioning
confidence: 99%